A 68-nW novel CMOS sub-bandgap voltage reference circuit. (July 2019) - Lei, Jianming; Wang, Zhen; Wang, Xiaolong
Abstract: This paper proposes a CMOS sub-bandgap reference (sub-BGR) circuit without resistors for ultra-low power applications. The BGR core circuit consists of a vertical PNP bipolar transistor, a temperature-compensation amplifier and a Proportional to Absolute Temperature (PTAT) voltage generator. The PTAT voltage generator consists of four p-type transistors and generates a positive temperature dependent voltage, which compensates for the negative temperature dependent base-emitter voltage in a PNP bipolar transistor. The circuit generates a sub-bandgap voltage of silicon. The sub-BGR is fabricated with 65-nm standard CMOS process with an area of 400 μm × 80  μm. Experimental results demonstrate that this sub-BGR circuit can generate a 202.8 mV reference voltage with a power consumption of 68 nW.